The Relationship Between theTendency for Negative Emotions and the Risk of Coronary Heart Disease - Đinđić, Vojislav M; Batinić, Borjanka; Vukosavljević-Gvozden, Tatjana (Psihološka istraživanja, 2018)
Goals: The main aimof the research was to determine the possible relationship between the tendency for negative emotions (operationalised through the traits of depression, anxiety and anger) and the risk of coronary heart disease. The secondaimwas to identify the combination of the examined emotional traits which best differentiates the persons with different states of health in the context of coronary heart disease. Method: The study sample consisted of 150 subjects divided into three groups: the personsdiagnosed with coronary heart disease, the personswith specific risk for coronary heart disease but without a diagnosis of coronary heart disease, and the personswith neither diagnosis nor risk of coronary heart disease. The following measurement instruments were applied: the Depressive Personality Scale, the Spielberger State-Trait Anxiety Inventory and the SpielbergerState-Trait Anger Expression Inventory. Results: The coronary heart disease group scored higher onall applied instruments compared to the group without specific risks. The subjects under the specific risk of coronary heart disease scored higher on the anxiety and depression inventory compared with the persons without specific risks. Canonical discriminant analysis revealed that the anxiety trait best differentiatesthe three groups, while the other two emotional traits proved to beredundant when it comes to prediction. Conclusions: The study results have shown a correlation between the traits of anxiety, anger and depression with the risk of coronary heart disease. The effects of the depression and anger traits can be almost completely explained by the correlation between the anxiety trait and the health status related to the coronary disease.
Keywords: tendency for negative emotions; risk; heart diseases; heart; emotions; depression; anger; anxiety